A systematic review of electronic assistive technology within supporting living environments for people with dementia. (November 2019) - Daly Lynn, Jean; Rondón-Sulbarán, Janeet; Quinn, Eamon; Ryan, Assumpta; McCormack, Brendan; Martin, Suzanne
Health and social care provision needs to change in order to meet the needs of an increase in the number of people living with dementia. Environmental design, technology and assistive devices have the potential to complement care, help address some of the challenges presented by this growing need and impact on the lived experience of this vulnerable population. This systematic review was undertaken to identify the research on the use of electronic assistive technology within long-term residential care settings. A total of 3229 papers published from the inception of each of the databases up until May 2016 were retrieved from searches in four major databases. Sixty-one were identified to be included in the review. The inclusion criteria were: original peer reviewed journals; an electronic assistive technology intervention; with residents or tenants living with dementia or their family or paid caregivers; in supported living environments or residential care. The data extracted from the included studies focused on the methodology, technology, outcomes and the role of people living with dementia within the research. Overall, an extensive variety of technical interventions were found, with a broad range of methodological heterogeneity to explore their effect. Additionally, wide-spanning outcomes to support the potential of technology solutions and the challenges presented by such intervention were found.